2007
DOI: 10.1002/art.22800
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival in psoriatic arthritis with calendar time

Abstract: Objective. To determine whether there has been a change in mortality rates over the last 3 decades in patients with psoriatic arthritis (PsA) whose cases were followed prospectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
80
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 16 publications
(19 reference statements)
0
80
3
Order By: Relevance
“…In contrast to reports from a Canadian referral-clinic population 18 , excess mortality in the Rochester cohort could not be demonstrated. The authors suggest that subjects with severe PsA are probably under-represented in this cohort compared to the Canadian cohort.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to reports from a Canadian referral-clinic population 18 , excess mortality in the Rochester cohort could not be demonstrated. The authors suggest that subjects with severe PsA are probably under-represented in this cohort compared to the Canadian cohort.…”
contrasting
confidence: 99%
“…Interestingly, an update from the Canadian cohort showed that the mortality risk has improved in recent decades. This could be due to earlier diagnosis and more aggressive treatment in the more recent followup period 18 . It should be noted, however, that in the current study 1 , 32% had radiographic erosions and 13% had osteolysis, indicating severe disease.…”
mentioning
confidence: 99%
“…114 Although survival of patients with PsA has improved in the past 2 decades, the mortality risk remains. 115 While the causes of death are similar to those of the general population, predictors for mortality include erosive disease at presentation as well as an elevated sedimentation rate. 116 Cardiovascular disease is among the leading causes of death among patients with PsA.…”
Section: Psoriatic Arthritismentioning
confidence: 99%
“…The SMR of antineutrophil cytoplasmic antibody-associated vasculitis ranged from 1.60 to 4.80 (36)(37)(38). The SMR of PsA patients was reported to be 1.62 in a cohort from the 1980s (32), but the SMR determined in the past decade was reported to be 0.56-0.82, i.e., not higher than that of the general population (30,31). Table 4 summarizes the SMRs for different rheumatic diseases found in different studies.…”
Section: Life Expectancy Smrs and Causes Of Death In Rheumatic Disementioning
confidence: 99%